Functionality of cassava genotypes for waxy starch - Santos, Thaís Barbosa dos; Carvalho, Carlos Wanderlei Piler de; Oliveira, Luciana Alves de; Oliveira, Eder Jorge de; Villas-Boas, Flávia; Franco, Célia Maria Landi; Chávez, Davy William Hidalgo (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to select cassava (Manihot esculenta) genotypes from the Brazilian germplasm bank with a functionality similar to that of waxy starch. A total of 881 genotypes were pre-selected using principal component analysis and hierarchical clustering, and their industrial potential was compared with that of the 7745-5WX waxy cassava and the WX-Maize waxy maize clones, both used as references. Two genotypes stood out: BGM0036 and BGM0083. Samples from these four genotypes were characterized by means of amylose content, scanning electron microscopy, X-ray diffraction, differential scanning calorimetry, paste viscosity, and chain-length distribution of amylopectin. The samples presented A-type crystallinity and no statistical differences (p > 0.05) regarding crystallinity degree (25.3 to 30.0), which shows similar proportions of the amylose/amylopectin fractions. No differences were observed in the microstructure of the cassava starches. Initial gelatinization temperature and amylopectin short chains presented a very strong negative correlation, indicating that a lower proportion of short chains of amylopectin results in a higher initial temperature of gelatinization. BGM0036 and BGM0083 show a low final viscosity, close to that of the waxy maize and cassava starches, being an alternative for use in different foods that require stability during freezing.